Finding Workable and Mutually Beneficial Solutions to Eradicate Illegal Gold Mining - Hasibuan, Ongku; Tjakraatmadja, Jann Hidajat; Sunitiyoso, Yos (UI Scholars Hub, 2021)
Illegal gold mining is a controversial activity. It provides livelihoods for rural communities in gold-rich areas and contributes to poverty alleviation; however, it also creates environmental devastation, losses to state revenue and often triggers social conflicts. Various eradication efforts have been made, ranging from persuasive approaches to harsh law enforcement involving the military and police, yet this illegal activity continues. This qualitative study aims to find and propose workable solutions to eradicate this activity, particularly in Indonesia. The study was conducted at two illegal- mining sites in Kalimantan, involving some 6,000 illegal-gold-miners. Data were collected through field observations and in-depth interviews with primary stakeholders, including authorities, perpetrators, and the community. The study identified eight sets of solutions to be implemented with an integrative approach, covering alternative livelihoods, cooperation and assistance, education and training, information dissemination, formalization, multi-sectoral collaboration, regulatory changes, and law enforcement. This paper contributes to model development in similar social circumstances and, in practice, provides workable solutions to illegal-gold-mining in other sites, particularly in Indonesia